KARAKTERISASI BUNGA DAN BUAH MANGGA HASIL PERSILANGAN ARUMANIS-143 (A) X SWARNARIKA (S), ARUMANIS-143 (A) X HADEN (H) DAN ARUMANIS-143 (A) X CARABAO (C) - Ristianing Dwi Fitriani; Mochammad Roviq; Tatik Wardiyati (BUANA SAINS, 2014)
Mango is one of export commodities of Indonesia. The research objective was to character-rize the mango flowers and fruit crossing of Arumanis-143 (A) x Swarnarika (S), Arumanis-143 (A) x Haden (H) and Arumanis-143 (A) x Carabao (C). Experiments through descriptive methods. Morphological characters of mango flowers included the emerging time of flower, flower per cluster numbers, flower per cluster numbers, fruit per cluster numbers, fruit set, color of flower stalk, flower petal color and the color of the ovary. Morphological characters of fruit were the fruit physiologival maturity days, numbers of fruit per tree, fruit weight per plant, fruit length, fruit width, fruit flesh thick, thickness of rind, fruit hardness, seed length, seed width, fruit shape, fruit tip shape, color ripe fruit peel, seed coat color and flesh color. Organoleptic characters were determined by attractive color, distinctive fragrance, fruit flavor and prime of fruit size. The results presented that Cluster 1 consisted of 34 or 97,14% progeny that have distances close kinship with the parent and has a similarity, cluster 2 only AS 2 has a far distance kinship with-parents Arumanis-143 or by 2.86%. Regarding affective test, 61.53% of progenies similar to Arumanis-143